Assessing the effects of exercise on post-partum fatigue symptoms: A systematic review and meta-analysis. (August 2022) - Kazeminia, Mohsen; Salari, Nader; Shohaimi, Shamarina; Akbari, Hakimeh; Khaleghi, Ali Asghar; Bazrafshan, Mohammad-Rafi; Mohammadi, Masoud
Abstract: Background: The level of activity in women who have given birth is very low despite the great benefits of exercise on their physical and mental health. There are some contradictories between the results of several preliminary studies on the effects of exercise on post-partum fatigue reduction. Therefore, the aim of this study was to assess the effects of exercise on decreasing postpartum fatigue in general and, specifically, in Iran using meta-analysis. Methods: In this study, the articles printed in international and national centres of SID, MagIran, IranMedex, IranDoc, Cochrane, Embase, ScienceDirect, Scopus, PubMed and Web of Science (WoS), were used to find the studies electronically published up to 2021. The studies' heterogeneity was examined using the I 2 index, and subsequently, a random-effects model was applied. Data analysis was performed within the Comprehensive Meta-Analysis software (version 2). Results: Finally, nine articles met the inclusion criteria in this systematic and meta-analysis review. The included samples were 456 patients in the intervention group and 446 in the control group. The mean score of fatigue after the intervention was 8.1 ± 1.1 lower than before intervention in the experimental group, and this difference was statistically significant (p ≤ 0.001). Conclusion: The results of this study indicate that exercise reduces postpartum fatigue, which can be used for counseling and treatment by gynecologists. Reduce postpartum problems in women and increase the quality of life after childbirth.